GPON over WDM-PON - Oliveira, Adolfo Manuel Melim Machado de (2014)
Due to the increased need for more bandwidth, access networks are evolving constantly. At the moment, GPON networks are the main choice in Europe, but due to the increased traffic in recent years, developing a new option for access networks defined NGPON2 as one of the main focuses in telecommunication research. In this document the current PON networks and the possible NGPON2 candidates will be studied. The main focus will be the possibility of designing a WDM-PON network while maintaining the main GPON architecture already implemented. By using SFPs, an example will be shown where a normal GPON transmission will be converted to another wavelength in order to show a possible implementation of a WDM network.